Cataclysmic Disturbances to an Intertidal Ecosystem: Loss of Ecological Infrastructure Slows Recovery of Biogenic Habitats and Diversity - Schiel, David R.; Gerrity, Shawn; Orchard, Shane; Alestra, Tommaso; Dunmore, Robyn A.; Falconer, Thomas; Thomsen, Mads S.; Tait, Leigh W. (Frontiers in Ecology and Evolution, 2021)
Understanding the resilience and recovery processes of coastal marine ecosystems is of increasing importance in the face of increasing disturbances and stressors. Large-scale, catastrophic events can re-set the structure and functioning of ecosystems, and potentially lead to different stable states. Such an event occurred in south-eastern New Zealand when a Mw 7.8 earthquake lifted the coastline by up to 6 m. This caused widespread mortality of intertidal algal and invertebrate communities over 130 km of coast. This study involved structured and detailed sampling of three intertidal zones at 16 sites nested into four degree of uplift (none, 0.4 – 1 m, 1.5 – 2.5 m, and 4.5 – 6 m). Recovery of large brown algal assemblages, the canopy species of which were almost entirely fucoids, were devastated by the uplift, and recovery over 4 years was generally poor except at sites with < 1m of uplift. The physical infrastructural changes to reefs were severe, with intertidal emersion temperatures frequently above 35oC and up to 50oC, which was lethal to remnant populations and recruiting algae. Erosion of the reefs composed of soft sedimentary rocks was severe, shifting sand and gravel covered some lower reef areas during storms, and the nearshore light environment was frequently below compensation points for algal production, especially of the largest fucoid Durvillaea antarctica/poha. Low uplift sites recovered much of their pre-earthquake assemblages, but only in the low tidal zone. The mid and high tidal zones of all sites remained depauperate. Fucoids recruited well in the low zone of low uplift sites but then underwent a severe heat wave a year after the earthquake that reduced their cover, followed by an increase in fleshy red algae, which then precluded recruitment of large brown algae. The interaction of species’ life histories and the altered physical and ecological infrastructure on which they rely are instructive for attempts to lessen manageable stressors in coastal environments to help future-proof against the effects of compounded impacts.